Social and cultural insights into healthy aging: A qualitative study from the South Indian City of Bengaluru, India - Manjulika Vaz; Priyanka Catherine Mani Kalliath; Deepika Nagaraja; Pretesh Rohan Kiran; Lavanya Garady; Arvind Kasthuri; Sucharita Sambashivaiah (Wolters Kluwer Medknow Publications, 2024)
Background: Qualitative methods through lived experience narratives provide relevant sociocultural insights into healthy aging. Objectives: The aim of this qualitative study was to explore social and cultural perceptions of healthy aging from older adults (OAs), their next of kin, and those involved in providing services to OAs in Bengaluru, India. Materials and Methods: We conducted in-depth interviews with 28 participants, all purposefully selected based on specific inclusion criteria, to get as varied a sample as possible. A pilot-tested, open-ended topic guide was used for every interview which was audio recorded with the permission of the respondent. Verbatim data were transcribed, reviewed for errors, and coded using NVivo 12 software and the framework analysis method of combining deductive and inductive codes. Results: In total, 794 codes covering concepts of healthy aging, enablers and threats to healthy aging, and perspectives for the future were categorized into four themes supporting healthy aging, namely emotional well-being and a sense of purpose, family and social support, financial security, and health-care access. Each of these had a bearing on the OA's physical and mental health. Across socioeconomic groups, a sense of purpose at the level of the self, family, and society emerged as a key emotional sustainer. Social and economic deprivations were key threats to healthy aging and hence required social security and governmental interventions. Conclusion: Sociocultural economic factors are key to healthy physical and mental aging in the context of India. The same factor could be an enabler and in its absence a threat.